The relationship between personality traits and psychotic like experiences in a large non-clinical adolescent sample. (January 2015) - Wiltink, S.; Nelson, B.; Velthorst, E.; Wigman, J.T.W.; Lin, A.; Baksheev, G.; Cosgrave, E.; Ross, M.; Ryan, J.; Yung, A.R.
Highlights: Personality traits and psychotic-like experiences are strongly associated. Severe psychotic-like symptoms cannot be explained by their link with depression. Neuroticism is most strongly linked with almost all psychotic-like symptoms. Abstract: Objective: The relationship between personality and psychosis is well established. It has been suggested that this relationship may be partly accounted for by higher levels of depression in individuals with certain personality traits. We explored whether the link between personality and psychotic symptoms is already apparent in adolescence, and if this association would still hold when depression was controlled for. Method: 654 secondary school students were surveyed via self-report questionnaires measuring the Five-Factor model of personality (NEO-FFI), depression (CES-D) and psychotic-like experiences (CAPE). Results: Positive associations were found between Neuroticism and all CAPE-subscales except Magical Thinking, which was in turn associated with all other personality traits when at high levels. Agreeableness was negatively associated with all CAPE-subscales, while Openness to Experience was only positively associated with Persecutory Ideas and Magical Thinking. After controlling for depression, many of the significant associations remained. Conclusion: Our findings suggest that the chance of having psychotic like experiences is more likely for adolescents with certain personality traits. These associations are not fully explained by depression, especially when psychotic experiences are at higher levels. Future research is needed to investigate if these personality traits might put a person at risk for the development of full-blown psychosis.